Management of Refractory Mechanical Ventilation Weaning in a Geriatric Neurocritical Patient with ARDS and COPD Using the ISCCM 2023 Guidelines: A Case Report - Sugeng Budi Santoso; Septian Adi Permana; Ryan Arifin (HM Publisher, 2026)
Mechanical ventilator weaning failure occurs in 20–30% of critically ill patients, with the risk significantly amplified by chronic obstructive pulmonary disease (COPD), acute neurological impairment, and severe hypoxemia. A 72-year-old female with COPD developed acute respiratory distress syndrome (ARDS) secondary to hospital-acquired pneumonia (HAP) following a re-craniotomy for an epidural hematoma. Following an initial extubation failure marked by hypercapnia (PaCO₂ 50.7 mmHg), the patient required reintubation. Her initial PaO₂/FiO₂ ratio of 127 mmHg indicated severe gas exchange impairment. Management utilized the 2023 Indian Society of Critical Care Medicine (ISCCM) guidelines. To facilitate weaning, the sedation strategy was transitioned from an initial thiopental infusion to dexmedetomidine, while continuous electrocardiographic monitoring was employed during the rapid correction of severe hypokalemia. The integration of early percutaneous dilatational tracheostomy (PDT), targeted diuresis, and resolution of ventilator-induced diaphragmatic dysfunction (VIDD) improved her PaO₂/FiO₂ ratio to 295 mmHg. In conclusion, successful ventilator liberation in complex neurocritical cases requires a rigorous, multidisciplinary approach. Integrating the ISCCM ABCDEFGHI bundle ensures the systematic correction of pathophysiological barriers, metabolic derangements, and sedation accumulation, leading to favorable clinical outcomes.